Ta‘lim jarayonida o‗quvchilarning insho yozish malakalarini oshirish - Ibodullayeva, I (SCIENCE and SOCIETY, 2023)
In this article, the development of thinking by teaching students to write essays in secondary schools. Opinions were expressed that the use of innovative technologies and modern methods in teaching essay writing creates the basis for quality education.
Keywords: Essay; «Intellect maps»; «Think and write»; oral and written speech; creative aсtivity; free thinking